Bank Profitability: Comparison Between Conventional And Islamic Bank In Indonesia - Firdayana Akhsan; Syamsu Alam; Andi Aswan (International Journal of Business and Quality Research, 2023)
This article discusses to analyse the differences of commercial banks in the United States. Indonesia by comparing Islamic banks and conventional banks as well as analysing the influence of independent variables such as loan to deposit ratio or financing to deposit ratio, non-performing loans or non-performing financing, and fee-based income on the profitability of Islamic banks and conventional banks from 2015-2022. Data obtained from 95 bank entities. The results of this study indicate that there are differences in variables that contribute to profitability found is the variable Non Performing Financing or Non Performing Loan in both conventional banks and Islamic banks. Overall this study found that between Islamic banks and conventional banks are significantly different in their operations and cause variables that have to do with operations to show significant differences supported by regression results which indicate that the NPL or NPF variable is the variable that most affects the profitability of Islamic banks and conventional banks.